General practitioner management related to skin cancer prevention and screening during standard medical encounters: a French cross-sectional study based on the International Classification of Primary Care. Issue 1 (30th January 2017) - Rat, Cédric; Houd, Sara; Gaultier, Aurélie; Grimault, Charlotte; Quereux, Gaelle; Mercier, Alain; Letrilliart, Laurent; Dreno, Brigitte; Nguyen, Jean Michel
Abstract : Objective: The aim of this study was to assess general practitioner (GP) management practices related to skin cancer prevention and screening during standard medical encounters. Setting: Data on medical encounters addressing skin cancer issues were obtained from a French database containing information from 17 019 standard primary care consultations. Participants: Data were collected between December 2011 and April 2012 by 54 trainees who reported the regular practice of 128 GPs using the International Classification of Primary Care. Outcome measures: Reasons for encounters and the following care processes were recorded: counselling, clinical examinations and referral to a specialist. Medical encounters addressing skin cancer issues were compared with medical encounters that addressed other health problems using a multivariate analysis. Results: Only 0.7% of medical encounters addressed skin cancer issues. When patients did require management of a skin cancer-related issue, this was more likely initiated by the doctor than the patient (70.7% vs 29.3%; p<0.001). Compared with medical encounters addressing other health problems, encounters that addressed skin cancer problems required more tasks (3.7 vs 2.5; p<0.001) and lasted 1 min and 20 s longer (p=0.003). GPs were less involved in clinical examinations (67.5% vs 97.1%; p<0.001), both complete (7.3% vs 22.3%, p<0.001) and partial examinations (60.2% vs 74.9%), and were less involved in counselling (5.7% vs 16.9%; p<0.001). Patients presenting skin cancer issues were referred to a specialist more often than patients consulting for other health problems (39.0% vs 12.1%; p<0.001). GPs performed a biopsy in 6.7% of all skin cancer-related encounters. Conclusions: This study demonstrates discrepancies between the high prevalence of skin cancer and the low rate of medical encounters addressing these issues in general practice. Our findings should be followed by qualitative interviews to better understand the observed practices in this field.